2015
DOI: 10.1021/acs.jpcb.5b07911
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Level Insights on Collagen–Polyphenols Interaction Using Spin–Relaxation and Saturation Transfer Difference NMR

Abstract: Interaction of small molecules with collagen has far reaching consequences in biological and industrial processes. The interaction between collagen and selected polyphenols, viz., gallic acid (GA), pyrogallol (PG), catechin (CA), and epigallocatechin gallate (EGCG), has been investigated by various solution NMR measurements, viz., (1)H and (13)C chemical shifts (δH and δC), (1)H nonselective spin-lattice relaxation times (T1NS) and selective spin-lattice relaxation times (T1SEL), as well as spin-spin relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…It is not only possible to directly probe the genuine inclusion of the guest in the CD cavity, but the large number of spectral parameters that can be measured and analysed give also access to unique qualitative and quantitative information. 7,9,[27][28][29][30] In the present work, we demonstrate that the measurement of different NMR parameters is extremely beneficial to investigate the sorption behaviour of βCD towards selected VOC in the DES reline (see Fig. 1 for structures).…”
Section: Introductionmentioning
confidence: 74%
“…It is not only possible to directly probe the genuine inclusion of the guest in the CD cavity, but the large number of spectral parameters that can be measured and analysed give also access to unique qualitative and quantitative information. 7,9,[27][28][29][30] In the present work, we demonstrate that the measurement of different NMR parameters is extremely beneficial to investigate the sorption behaviour of βCD towards selected VOC in the DES reline (see Fig. 1 for structures).…”
Section: Introductionmentioning
confidence: 74%
“…It is a polyphenol that binds to collagen with a high affinity and increases its thermal and enzymatic stability [ 18 , 25 ]. The stabilization of collagen by EGCG is thought to involve hydrogen-bonding and hydrophobic interactions between EGCG’s galloyl moieties and side-chain functional groups on the collagen molecule [ 18 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A remarkably high modulus of elasticity was found for the dentin treated with VV at 6.5%. At the monomeric level of catechins, it was shown that galloylated moieties have higher potency to enhance the dentin-collagen cross-linking compared to their non-galloylated counterparts on initial treatment [19] and greater collagen stabilizing effect against bacterial proteolytic degradation [4]. Additionally, it is not only the hydroxy groups that contribute to the cross-linking, but the entire PAC skeleton including the aromatic rings that can lead to hydrophobic interactions.…”
Section: Discussionmentioning
confidence: 99%